(3GdaJhMGJ GdeQGOjI aj GdLgGJ GdjeGfjIs - (3YHO Gddg Hf UdGM GdOjf Hf OGhO Hf Ydj Hf OGYQ,J (B1013 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd eQGOg YfhGfkG dUMGFa GdGYJHGQ s
(3BNQgG (B:s
(3hgG CfG bO bOeJ Hjf jOi HeG CJjJ ef PcQge HeG jLH Ydi hGdQL MGUd dOi hdf jNjH Cedi ai aVGFd Gddg HCf jMSf Edi s
(3QJHg Ydi NeS ebOeGJ hKdGKI YTQ HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B93s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B635 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B195 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs